How Apple revolutionized our world. - Theroux, Paul.
Steve Jobs's dazzling inventions have forever changed us.
Keywords: Jobs, Steve -- 1955-2011.; Apple Computer, Inc; iPod (Digital music player); iPhone (Smartphone); iPad (Computer); Video chatting